The Influence of Industry Type, Underwriter Reputation, and Return on Assets (ROA) on IPO Stock Performance Before and After COVID-19 - Yunita Ardella Putri; Fajri Adrianto (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to analyze the influence of industry type, underwriter reputation, and return on assets (ROA) on the performance of IPO stocks before and after COVID-19. The research is motivated by the issue that the COVID-19 pandemic, which began in 2020, had a significant impact on the global economy, including Indonesia’s capital market. The Jakarta Composite Index (IHSG) sharply declined at the onset of the pandemic, yet Initial Public Offering (IPO) activity showed an increase. This raised questions about the factors that influence IPO stock performance during the period before and after the pandemic. The research method uses a quantitative approach with multiple linear regression analysis. Data was collected from 56 companies that conducted IPOs during the period 2018–2022, including financial statements and closing stock prices. The results indicate that industry type and underwriter reputation have a significant impact on IPO stock performance, both before and after the pandemic. However, ROA did not show a significant effect. These findings provide important insights for investors, companies, and regulators in understanding the dynamics of the capital market amid global economic changes.